Development of Interactive Media Using the Quantum Learning Method in Geography Education at Seririt 1 Public High School - Pandiangan, Raymond; Citra, I Putu Ananda; Sriartha, I Putu (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aims to describe the validity, practicality, and effectiveness of interactive learning media based on Quantum Learning using the Quizizz application in Geography lessons for grade XI students at SMA Negeri 1 Seririt. This research is of the R&D type, adapting the ADDIE model. The subjects of this research are one Geography teacher and 34 students from class XI-4 at SMA Negeri 1 Seririt. Research data was collected through expert validation, teacher and student responses, pretest, and posttest. Data analysis was conducted using descriptive quantitative methods. The research results are as follows: (1) the validity of the media has an average score of 81.23 (very suitable), (2) the practicality of the media has an average score of 91.65 (very practical), and (3) the effectiveness of the media shows a high average N-Gain score of 0.74 (73.75%). Therefore, the interactive learning media based on Quantum Learning assisted by the Quizizz application is deemed valid, practical, and effective as a learning tool for Geography that supports the improvement of concept understanding among Grade XI-4 students.